Importance–performance analysis and improvement of an urban park's cultural ecosystem services based on users' perspectives: A Beijing case study. Issue 2 (4th March 2023) - Gai, Shijie; Fu, Jiaming; Rong, Xiao; Dai, Linlin
ABSTRACT: To construct urban parks in high-density urban areas is an important strategy for dealing with urban problems caused by rapid urbanization and global climate change, and even small-scale parks can provide cultural ecosystem services (CES). However, the differences in the users' perspectives of the supply and demand of CES in small-scale urban parks have been underexplored. Therefore, this study takes a newly-built park in a complex urban block in Beijing as a case. It studies different users' perspectives of the urban park's CES using importance–performance analysis. The results show that: (1) Users' perspectives of the importance and performance of the park's CES significantly differed, and "Recreation" was the sub-item that had the largest gap between supply and demand. (2) Users' spatial and temporal profiles were the main factors that affected their CES perspective. (3) Users most agreed with improving the two CES sub-items of "Rest" and "Recreation" through design optimization. This study suggests that policymakers and planners can formulate targeted promotion strategies based on an understanding of the mismatch between the supply and demand of CES in urban parks. It can also provide guidelines for the construction and optimization of parks in central areas of high-density cities. GRAPHICAL ABSTRACT: uf0001